Trabalho de conclusão de curso: pastelaria - GOMES, Mellyne; NASCIMENTO, Kethlyn; SOUZA, Vinicius; VITÓRIA, Andreia (238, 2019)
Nosso trabalho trata a respeito da administração e tentativa de melhorias de uma empresa já pronta. Buscamos de inúmeras maneiras aumentar a qualidade da empresa escolhida. A empresa que escolhemos e uma pastelaria, na qual a dona prefere ser chamada de “tia”. Lá além da venda de pastéis, há a venda de lanches, tais como: hot dog’s, salgadinhos, entre outros. Buscamos diversas oportunidades de a empresa crescer, com auxílio de nossos conhecimentos, adquiridos ao longo do curso técnico em administração.

Our work deals with the administration and attempts to improve an already ready-made company. We seek in countless ways to increase the quality of the chosen company. The company we chose is a pastry shop, in which the owner prefers to be called “aunt”. There, in addition to the sale of pastries, there is the sale of snacks, such as: hot dogs, snacks, among others. We seek several opportunities for the company to grow, with the help of our knowledge, acquired during the technical course in administration.
Course Completion Work: pastry
Keywords: Administração de empresa; Consultoria de empresas; Prestação de serviço; Gestão da qualidade; Gestão e Negócios